Jaring estetika suara-suara kelas - Hudayat, A. Y., 1970- (Jatinangor : Sastra Unpad Press, 2010)
Literary criticism on Sundanese novels.
Includes bibliographical references (p. [167]-170).
Keywords: Sundanese fiction -- History and criticism